An upper-lower solution method for the eigenvalue problem of Hadamard-type singular fractional differential equation - Zhang, Xinguang; Kong, Dezhou; Tian, Hui; Wu, Yonghong; Wiwatanapataphee, Benchawan (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, we are concerned with the eigenvalue problem of Hadamard-type singular fractional differential equations with multi-point boundary conditions. By constructing the upper and lower solutions of the eigenvalue problem and using the properties of the Green function, the eigenvalue interval of the problem is established via Schauder’s fixed point theorem. The main contribution of this work is on tackling the nonlinearity which possesses singularity on some space variables.
Keywords: Hadamard-type fractional differential equation; upper-lower solution method, eigenvalue problem; singularity